Day 1 Panel 2: How Bias Manifests in New York State's Family Law System - Hamra Ahmad; Jacqueline Franchetti; Linda Lopez; Carolyn Springer; Shain Filcher; Rachel Braunstein (Columbia Journal of Gender and Law, 2023)
Day 1 – October 13, 2022 Keynote Panel 2: How Bias Manifests in New York State's Family Law System